Social Status and Views as Factors of Applying for Psychological Assistance - SERGEY, Tkach; ANNA, Kochetkova; MARIA, Sennikova; MAYA, Rusakova (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose: The article examines the extent to which people are willing to accept psychological help based on their attitudes and social status. The study's primary purpose is to determine the role of social status and ideas about psychological help in a person's readiness to receive it.Methodology:The empirical basis of the study was a telephone survey. The sample population (547 people) was representative by gender and age for St. Petersburg. The methodological model of the study is based on the theory of M. Kovalevsky about the pluralistic nature of social experience and motivation. The obtained empirical data were analyzed using a weighted least squares regression model. The dependent variable is whether residents have experience in receiving psychological help.Findings:At the same time, no significant connection was found between the experience of seeking psychological help and the level of income, as well as the age of the respondents, which requires further research on the given topic. The findings demonstrate that being unemployed has a more pronounced positive role in the decision to seek help, despite earlier studies showing the opposite.Implication:The results of the work also contribute to the academic debate about the nature of the emergence of communication groups.